2023
DOI: 10.3389/fpsyg.2022.1084963
|View full text |Cite
|
Sign up to set email alerts
|

Authentic leadership, perceived organizational support, and psychological capital: Implications for job performance in the education sector

Abstract: The present study sifts the indirect role of psychological capital (PsyCap) in linking authentic leadership (AL) and job performance (JP). Furthermore, this study investigates the interplay of AL and perceived organizational support (POS) in PsyCap. We tested these assumptions through PROCESS macro with two sources of data collected from 350 employees and their respective colleagues working in education sector organizations in China. The study findings established that AL positively influences employee perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Universities should give top priority to mental health services and initiatives that promote a positive and supportive environment, as psychological wellbeing has a significant impact on these factors. Despite the recognized significance of psychological capital (PsyCap) in influencing organizational and academic results, there has been a lack of research conducted on this subject in educational environments (Sarwar et al, 2023). This research contributes to the existing knowledge by showcasing the positive impact of PsyCap on students' academic performance in the classroom.…”
Section: Discussionmentioning
confidence: 89%
“…Universities should give top priority to mental health services and initiatives that promote a positive and supportive environment, as psychological wellbeing has a significant impact on these factors. Despite the recognized significance of psychological capital (PsyCap) in influencing organizational and academic results, there has been a lack of research conducted on this subject in educational environments (Sarwar et al, 2023). This research contributes to the existing knowledge by showcasing the positive impact of PsyCap on students' academic performance in the classroom.…”
Section: Discussionmentioning
confidence: 89%
“…26 Many studies have revealed that PsyCap is a positive and valuable resource that promotes job satisfaction and job performance. [27][28][29][30] PsyCap is a defense mechanism against unfavorable employee outcomes such as resignation plans and pessimism. 31 Based on the Job Demands-Resources (JD-R) model, employees who are stressed at work may experience emotional exhaustion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, a study conducted with 350 nurses across four public hospitals employed structural equation modeling and found that job embeddedness mediates the relationship between psychological capital and employee performance [ 2 ]. In a recent study among Chinese educational organizations employees, findings revealed that authentic leadership positively influences job performance (JP) directly and indirectly through PC, with perceived organizational support moderating the impact of authentic leadership on PC [ 10 ].…”
Section: Introductionmentioning
confidence: 99%